Multimodality disciplinary thoughts and the challenge of diversity - Wildfeuer, Janina, 1984-; Pflaeging, Jana, 1985-; Bateman, John A.; Seizov, Ognyan; Tseng, Chiao-I, 1976- (De Gruyter Mouton, 2019)
Multimodality's popularity as a semiotic approach has not resulted in a common voice yet. Its conceptual anchoring as well as its empirical applications often remain localized and disparate, and ideas of a theory of multimodality are heterogeneous and uncoordinated. For the field to move ahead, it must achieve a more mature status of reflection, mutual support, and interaction with regard to both past and future directions. The red thread across the disciplines reflected in this book is a common goal of capturing the mechanisms of synergetic knowledge construction and transmission using diverse forms of expressions, i.e., multimodality. The collection of chapters brought together in the book reflects both a diversity of disciplines and common interests and challenges, thereby establishing an excellent roadmap for the future. The contributions revisit and redefine theoretical concepts or empirical analyses, which are crucial to the study of multimodality from various perspectives, with a view towards evolving issues of multimodal analysis. With this, the book aims at repositioning the field as a well-grounded scientific discipline with significant implications for future communication research in many fields of study. -- Provided by publisher